Impact of Employer Coverage on Elective Oocyte Cryopreservation: A Study of Graduate Students [9B]. (May 2018) - Turocy, Jenna; Cardozo, Eden; James, Kaitlyn; Freeman, Marlene; Toth, Thomas
Abstract : INTRODUCTION: Our aim is to assess female graduate student's attitudes toward elective oocyte cryopreservation (OC) and the potential impact of employer coverage on their family planning decisions. METHODS: This cross-sectional study was performed via an online survey distributed to 2, 314 female graduate students enrolled in 5 graduate degree programs including masters, doctorate, MBA, law and dental programs from May through October 2016. Survey answers were stratified by demographic factors including relationship status and graduate degree. RESULTS: 171 female graduate students completed the survey. The majority of respondents were between the ages of 21 and 30 (80%) and had no children (95%). The most common reasons for deferring childbearing were professional goals (63%), followed by no partner (18%) or financial (11%). The majority of participants (97%) have heard of elective OC, citing their largest concern was cost (59%) and success rates (14%). Without employee coverage, only 10% would consider elective OC. However if offered employer coverage for OC, an additional 39% would consider OC and 20% would delay when they planned to have children. Participants enrolled in Dental and Law programs were more likely to delay childbearing if provided employer coverage for OC compared to all other programs (p<0.05). CONCLUSION: Among female graduate students surveyed, more women would consider OC and delay childbearing if financial coverage were provided by their employer. As more companies offer coverage for OC, further research is needed to better understand how employer coverage for OC may impact a woman's family planning decisions and potentially lead to a delay in childbearing.